The Deer Hunter: The Unintended Effects of Hunting Regulations - Conlin, Michael; Dickert-Conlin, Stacy; Pepper, John (The Review of Economics and Statistics, 2009)
To control the deer population, state game commissions regulate the types of deer that can be legally harvested. These regulations, however, might have an unintended effect on hunting-related accidents by changing the care hunters take when firing their rifles—a moral hazard effect—or changing the composition of hunters. Using detailed data on hunting accidents and regulations in Pennsylvania counties from 1990 to 2005, we find compelling evidence that harvesting restrictions increase the care hunters take in a manner consistent with moral hazard. Thus, these regulations have a positive safety externality.